FOREIGN APPROACHES TO HEALTHCARE SYSTEM FINANCING - Samandarov Dostonbek (Modern American Journals, 2025)
This article analyzes the mechanisms for evaluating treatment effectiveness, outcome-based financing, diagnosis-related group (DRG) payment systems, and centralized fund distribution experiences in Sweden, Germany, Austria, and South Korea. It discusses their significance and the phased implementation of Uzbekistan's state medical insurance model.
Keywords: Healthcare financing, outcome-based financing, DRG, medical insurance, centralized fund